A SERVICE EVALUATION OF A SPECIALIST COMMUNITY PALLIATIVE CARE OCCUPATIONAL THERAPY (OT) SERVICE. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Phipps, Kerrie; Cooper, Jan
Abstract : Background: Palliative care OT is an integral part of comprehensive end of life care, maximising patients' independence and maintaining independent living. However studies have highlighted that professionals often have an inadequate understanding of OT interventions, and as a result patients are not referred. This has led to a concern that some patients, who are experiencing functional difficulties in line with disease progression, may not receive the OT support they require. Aim: This project took place in 2012 and was a service evaluation of an existing Specialist Community Palliative Care OT Service. It aimed to evaluate the service from a professional users' perspective to identify areas of good practice and those requiring further development/improvement. Methods: Two data collection methods were selected to collect evaluative data: An online questionnaire to 100 core Gold Standard Framework (GSF) professional group members who had referred to the service in the past 12 months. Two focus groups of GSF group members to expand on the emergent themes identified in the analysis of the questionnaire results. Results: 58 out of 100 (58%) online questionnaires were completed and a total of 26 professionals attended the focus group meetings. Results of the evaluation demonstrated Specialist Community Palliative Care OT has a significant impact on: maintaining patient's independence; comfort, and quality of life. Professionals associated the service with supporting patients' preferred place of care; improved patient outcomes, and valued it in terms of its ability to support them in addressing the needs of their patients. Factors in ensuring patients receive timely and appropriate OT interventions were: clear communication pathways and education and information strategies regarding the role of the community palliative care OT Conclusion: The results of this service evaluation demonstrate the importance/contribution of specialist palliative care OT in comprehensive end of life care. However the results also demonstrated the need for education of the role of OT in palliative care, ensuring all patients receive this specialist support.